2020
DOI: 10.1177/0003134820949511
|View full text |Cite
|
Sign up to set email alerts
|

Frailty as a Predictor of Postoperative Morbidity and Mortality Following Liver Resection

Abstract: Background Liver resection is commonly performed among patients at risk of being frail. Frailty can be used to assess perioperative risk. Thus, we evaluated frailty as a predictor of postoperative complications following liver resection using a validated modified frailty index (mFI). Methods A retrospective cohort of consecutive patients undergoing liver resection (2011-2018) were stratified according to the mFI and classified as the following: high (≥.27) and low mFI (<.27). The effect of mFI on postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Numerous studies have examined predictors of adverse cardiovascular outcomes and mortality following Eur J Anaesthesiol 2022; 39:145-151 noncardiac surgery. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] These studies differed in their selection of patients, types of surgery, proportions of emergency procedures and extent of postoperative morbidity. We aimed to identify the definition of intraoperative tachycardia that has the strongest association with adverse postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have examined predictors of adverse cardiovascular outcomes and mortality following Eur J Anaesthesiol 2022; 39:145-151 noncardiac surgery. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] These studies differed in their selection of patients, types of surgery, proportions of emergency procedures and extent of postoperative morbidity. We aimed to identify the definition of intraoperative tachycardia that has the strongest association with adverse postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the association between poor outcomes and high frailty scores in patients with various disorders, such as cardiovascular diseases, 24 infectious diseases, 25 liver disease, 26 or malignant diseases including gastrointestinal cancer. 4 , 5 , 6 , 7 , 8 , 27 As for hepatic resection, 11 studies 5 , 6 , 7 , 8 , 9 , 10 , 11 , 13 , 14 , 15 , 16 are available to date, among which 10 showed the usefulness of frailty scoring in predicting mortality, morbidity, or prognosis after hepatectomy. Tanaka et al 7 conducted a prospective multicenter study using the Kihon checklist and demonstrated that high frailty was an independent risk factor for age‐related events (major respiratory complications, major cardiac events, delirium requiring medication, transfer to rehabilitation facility, and dependency).…”
Section: Discussionmentioning
confidence: 99%
“…These patients are often associated with frailty—an impaired physiological condition resulting from aging that increases vulnerability to stress 2,3 . Recently, several studies have reported that frailty is a more significant risk factor than aging for postoperative complications or long‐term survival after surgery for various cancers, including gastrointestinal cancer 4–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is a syndrome commonly observed in the elderly [ 65 ]. It encompasses a state of increased vulnerability to environmental factors, but with the reversibility of returning to a healthy state with appropriate intervention [ 66 , 67 , 68 ]. There are physical, psychological and social factors that contribute to frailty [ 65 ].…”
Section: Frailty In Liver Disease: Its Definition and Prevalencementioning
confidence: 99%